Transformational Leadership and Innovative Work Behavior in Police Organizations: The Mediating Roles of Digital Competence and Digital Culture - Chandra Nilawati; Desi Tri Kurniawati; Misbahuddin Azzuhri (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Digital transformation demands greater innovation capacity in public sector organizations. The rapid development of digital technology and the increasing complexity of public service demands require police organizations to adapt through stronger innovation capabilities, digital readiness, and supportive leadership. However, continues to face challenges such as uneven digital skills, weak dissemination of digital training outcomes, hierarchical barriers, and limited motivation toward innovation. These conditions indicate the need for leadership that is capable of inspiring change and fostering an innovative climate. This study examines the effect of transformational leadership on innovative work behavior with digital competence and digital culture as mediating variables. This study employs a quantitative research method. Using transformational leadership theory, Kurt Lewin’s Change Theory, and Expectancy Theory. The research also addresses the inconsistency of previous findings regarding the relationship between transformational leadership and innovative work behavior. Data were collected using a structured questionnaire and analyzed using PLS-SEM. The results are expected to demonstrate that transformational leadership positively influences innovative work behavior, both directly and indirectly, through digital competence and digital culture. This study contributes theoretically to human resource management literature and provides practical insights for police organizations seeking to strengthen innovation and digital transformation.